USING SOCIAL MEDIA TO IMPROVE STUDENTS’ SPEAKING SKILL - Kamaruddin, Adinda; Jabu, Baso; Muhayyang, Maemuna (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The purpose of this study was to determine whether the use of Social Media improves students' speaking accuracy or not. The pre-experimental design was a method used by the Researcher with the quantitative approach that gives pre-test, treatment and last was post-test. The population is class XI SMAN 8 Makassar. The sample of students consisted of 20. This research used an instrument a speaking test which was given as a pretest, and a post-test. The results of this study proved that the students' scores before treatment and students' scores after treatment there was different score, Students' speaking accuracy after the use of social media can improve or get better than before the use of social media. It can be concluded that the use of social media Wa and Youtube has improved students' speaking accuracy in eleven-grade students of SMAN 8 Makassar.